Impact of black silicon on light‐ and elevated temperature‐induced degradation in industrial passivated emitter and rear cells. (4th December 2018) - Pasanen, Toni P.; Modanese, Chiara; Vähänissi, Ville; Laine, Hannu S.; Wolny, Franziska; Oehlke, Alexander; Kusterer, Christian; Heikkinen, Ismo T.S.; Wagner, Matthias; Savin, Hele
Abstract: Light and elevated‐temperature induced degradation (LeTID) is currently a severe issue in passivated emitter and rear cells (PERC). In this work, we study the impact of surface texture, especially a black silicon (b‐Si) nanostructure, on LeTID in industrial p‐type mc‐Si PERC. Our results show that during standard LeTID conditions the b‐Si cells with atomic‐layer‐deposited aluminum oxide (AlO x ) front surface passivation show no degradation despite the presence of a hydrogen‐rich AlO x /SiN x passivation stack on the rear. Furthermore, b‐Si solar cells passivated with silicon nitride (SiN x ) on the front lose only 1.5%rel of their initial power conversion efficiency, while the acidic‐textured equivalents degrade by nearly 4%rel under the same conditions. Correspondingly, clear degradation is visible in the internal quantum efficiency (IQE) of the acidic‐textured cells, especially in the 850 to 1100‐nm wavelength range confirming that the degradation occurs in the bulk, while the IQE remains nearly unaffected in the b‐Si cells. The observations are supported by spatially resolved photoluminescence (PL) maps, which show a clear contrast in the degradation behavior of b‐Si and acidic‐textured cells, especially in the case of SiN x front surface passivation. The PL maps also suggest that the magnitude of LeTID scales with surface area of the texture, rather than wafer thickness that was recently reported, although the b‐Si cells are slightly thinner (140 vs 165 μm). The results indicate that b‐Si has a positive impact on LeTID, and hence, benefits provided by b‐Si are not limited only to the excellent optical properties, as commonly understood. Abstract : We study the impact of surface texture, especially a black silicon (b‐Si) nanostructure, on light and elevated‐temperature induced degradation (LeTID) in p‐type mc‐Si PERC. Industrial b‐Si cells exposed to typical degradation conditions maintain their performance, while acidic‐textured equivalents degrade by nearly 4%rel . The results suggest that b‐Si has a positive impact on LeTID, and hence, benefits provided by b‐Si are not limited only to the excellent optical properties, as commonly understood.